The Impact of Nutritional Supplements on Sarcopenia: A Systematic Review and Meta-Analysis - Mansoor, Usman; Edano, Donna; Usman, Maaza; Habib, Usman (Curēus (Palo Alto, CA), 2025)
Sarcopenia is characterized by progressive loss of muscle mass, strength, and function, and poses a major risk for permanent disability and poor quality of life in elderly patients. Nutritional supplements have been proposed as a potential intervention; however, findings in the literature have been inconsistent, necessitating a comprehensive systematic review and meta-analysis. Therefore, the present review aimed to assess the impact of nutritional supplements on the progression and management of sarcopenia-associated problems, such as muscle mass, strength, and function. A comprehensive literature search was performed on different electronic databases, such as PubMed, Scopus, ScienceDirect, The Cochrane Library, and Google Scholar. Studies assessing the impact of nutritional supplements on muscle mass and strength functions in sarcopenia patients were included. Narrative synthesis was performed for the presentation of the general characteristics of studies, interventions, and outcomes, while meta-analysis was performed using the random effect model via RevMan 5.4 at the significance level of 0.05. Funnel plots were used for the interpretation of publication bias, methodological quality assessment of randomized controlled trials (RCTs) was performed using the Cochrane Risk of Bias-2.0 (RoB 2) assessment tool, and certainty of evidence using the GRADE (Grading, Reporting, Assessment, Development, and Evaluation) framework. After screening, 28 studies were included in the review, which focused on nutritional supplements containing protein, amino acids, vitamin D, creatine, omega-3, vitamin B12, zinc, magnesium, and other nutrients. These supplements demonstrated significant differences in improving handgrip strength [std. mean difference (MD): -0.10, 95% confidence interval (CI): -0.21 to 0.00, p=0.05, I =0%], skeletal muscle mass index [std. MD: 0.29 (95% CI: 0.04 to 0.53), p=0.02, I =0%], total fat mass [std. MD: 0.21 (95% CI: 0.01 to 0.41) p=0.04, I =5%]. In contrast, a non-significant difference was observed in skeletal muscle mass [std. MD: 0.16 (95% CI: -0.02 to 0.33) p=0.08, I =0%], appendicular lean mass (std. MD: -0.03 (95% CI: -0.22 to 0.16) p=0.76, I =0%], gait speed [std. MD: 0.01 (95% CI: -0.23 to 0.21) p=0.95, I =65%], and adverse events odds ratio (OR): 1.08 (95% CI: 0.80-1.45) p=0.60, I =0%]. No publication bias was observed, and methodologically, most of the studies were found to have a low RoB, except for five RCTs, which had some concerns in the randomization process. Outcomes, like handgrip strength, skeletal muscle mass index, and adverse events, showed a high certainty of evidence. The skeletal muscle and appendicular lean mass had a moderate certainty of evidence, and gait speed had a low certainty of evidence. This study indicates that nutritional supplements demonstrated potential in improving muscle strength. However, further long-term, multicenter, and longitudinal studies are required to validate these findings.